Safety in Kitchen Using IOT - Gholse, Nehal; Khetan, Sajal; Kanhegaonkar, Pranav; Bairagi, V.K (International Journal of Computer Sciences and Engineering, 2021)
Gas stoves are one of the most important assets in the kitchen. All the cooking activities are carried out with the help of this apparatus. Through our project, we are trying to bring into focus those areas which can cause danger in the kitchen. Through our project, we are taking some important factors into consideration that will help the user to avoid those harmful situations. We have observed that most of the accidents in the kitchen take place due to the less careful behaviour of the user. Our project focuses on the idea to provide safety to the user hence avoiding accidents due to flame, gas leakage, or spillage of the flame. Project is the real-time application of the embedded system to turn off the gas stove knob in case of an emergency situation using a reverse gear mechanism. There are three cases in which the automatic turning off the gas stove will take place. 1) In the absence of a user for a set amount of time 2) When smoke or gas leakage is detected. 3) When flame blows off accidently.